Participating in Parliamentary Politics: Experiences of Indonesian Women 1995-2010 - Sharyn Graham Davies; Nurul Ilmi Idrus (Journal of Indonesian Social Sciences and Humanities, 2010)
This article concerns itself with womens participation in politics and, more specifcally, the representation of women in elected legislatures, in Indonesia between 1995 and 2010. The article gives readers a brief overview of the various ways that Indonesian women participate in politics. Examples are given of women being traditional rulers, having political authority, exercising power, becoming presidents and cabinet ministers, participating in protest movements, and being elected to parliament. The article then moves to focus more specifcally on the election of women to the Indonesian parliament. The article analyses positive developments that have occurred in the past decade to facilitate womens entry to parliamentary politics. Although numerous positive developments have indeed taken place, the article argues that women are still hindered in their attempts to get elected to parliament. Drawing on indepth interviews, literature reviews, statistical analysis, and long-term ethnographic research, the authors identify some of the factors limiting womens election, including the restrictive limited model of womanhood advocated in Indonesia, declining cronyism, the ineffectiveness of the thirty per cent quota, the reputation politics has of being dirty, the in?uence of religion, and the large sums of money candidates need to support their election campaigns.